Long‐term results of endoscopic resection for type I gastric neuroendocrine tumors. Issue 2 (25th October 2013) - Uygun, Ahmet; Kadayifci, Abdurrahman; Polat, Zulfikar; Yilmaz, Kemalettin; Gunal, Armagan; Demir, Hakan; Bagci, Sait
<x xml:space="preserve">Abstract</x> Background A number of different therapies, including endoscopic resection, have been suggested for the treatment of Type 1 gastric neuroendocrine tumors (NETs). The current study aimed to determine the long‐term efficacy of endoscopic resection for Type 1 gastric NETs. Methods Twenty‐two patients (from 1999 to 2012) with Type 1 gastric NETs were included in the study. All patients were treated with endoscopic resection and received regular followed‐up appointments at a tertiary referral center. Results All patients were initially diagnosed with hypergastrinemia, atrophic gastritis and intestinal metaplasia. Polyps' diameters were >1 cm in 4 patients, and between 0.5 and 1 cm in 18 patients. All detectable lesions were successfully resected. One patient required surgery due to gastric perforation during endoscopic mucosal resection. Recurrence was detected in four patients (18%) and endoscopic resection was performed again. Local or distant metastasis was not observed in any patient during follow‐up. Median follow‐up time was 7 years, with a maximum of 14 years. Seventeen patients (78%) completed a 5‐year follow‐up period, and overall disease‐free survival rate was 100%. Conclusions Long‐term follow‐ups with 22 patients suggest that endoscopic resection of Type 1 gastric NETs is a safe and effective treatment option with a relatively low recurrence rate. J. Surg. Oncol. 2014 109:71–74. © 2013 Wiley Periodicals, Inc.